How Do Neurons Signal Itch? - Schmelz, Martin (Frontiers in Medicine, 2021)
Mechanistic theories of itch are based on neuronal specificity, stimulus intensity, and temporal or spatial discharge patterns. Traditionally, these theories are conceptualized as mutually exclusive, assuming that finding evidence for one theory would exclude the others and could sufficiently explain itch. Current experimental data primarily support the specificity or pattern theory of itch. However, in contrast to an assumed inherent exclusivity, recent results have shown that even within itch-specific pathways in the spinal cord, temporal discharge patterns are important as sustained pruriceptor is required to allow successful transsynaptic signal progression. Also, optogenetic activation of pruriceptors suggest that the combination of neuronal specificity and temporal pattern determines the sensory effect: tonic activation of pruriceptors is required to induce scratching behavior whereas short-lasting stimulation rather causes withdrawal. In addition to the mere duration of discharge, also the temporal pattern or spatial aspects could critically contribute to elicit pruritus instead of pain. Basic neurophysiological studies trying to validate neuronal theories for pruritus in their pure form provide unitary concepts leading from neuronal discharge to the itch sensation. However, the crucial clinical questions have the opposite perspective: which mechanisms explain the chronic itch in a given patient or a given disease? In trying to solve these clinical problems we should not feel bound to the mutual exclusive nature of itch theories, but rather appreciate blending several theories and also accept combinations of itch and pain. Thus, blended versions of itch theories might better suffice for an explanation of chronic itch in patients and will improve the basis for mechanistic treatment options.